Catalytic Scenarios Over Metal-Carbon Interaction Interface - Xing, Liwen; Jin, Yujuan; Weng, Yunxuan; Ji, Yongjun (Frontiers in Chemistry, 2021)
The numerous efforts have been devoted to investigating the catalytic events and disclosing the catalytic nature over metal-carbon interaction interface. Nevertheless, the local deconstruction of catalytically active metal-carbon interface was still missing. Herein, the selected four types of landmark catalytic paradigms were highlighted, which was expected to clarify their essence and thus simplify the catalytic scenarios over metal-carbon interface—carbon-supported metal nanoparticles, carbon-confined single-atom sites, chainmail catalysis and Mott-Schottky effect. The potential challenges and new opportunities were also proposed in the field. This perspective is believed to give an in-depth understanding of the catalytic nature over metal-carbon interaction interface and in turn provide a rational guidance to the delicate design of novel high-performance carbon-supported metal catalysts.